The Influence of Efficacy and Threat Messages on the Intention to Complete the Covid-19 Booster Vaccination: Experimental Study of University Students - Ayunarendra, Victoria Kesha; Wiyanto, Siko; Nurdin, Ivan (Newinera Publisher, 2024)
The COVID-19 pandemic that has occurred since 2020 has not ended until now. The government has made various countermeasures, one of which is accelerating the third or booster vaccine program. However, research results show that the number of people who have received the booster vaccine is still very far from the government's target. One of the reasons why the number of booster vaccine recipients is far from the target is due to people's reluctance to receive booster vaccines. Therefore, effective communication is needed to overcome this problem. Based on previous research, the fear approach is considered an effective way to promote health messages. So, this research tries to use the Extended Parallel Processing Model (EPPM) theory to see the influence of efficacy and threat messages on intentions to take a booster vaccine. The results of this study were that there was no change in intention to carry out booster vaccination in respondents who were given a high threat or a low threat.